A dual-systems perspective on temporal cognition: Implications for the role of emotion. (2019) - Nuyens, Filip M.; Griffiths, Mark D.
Abstract: This commentary explores how emotion fits in the dual-systems model of temporal cognition proposed by Hoerl & McCormack. The updating system would be affected by emotion via the attentional/arousal effect according to the attentional gate model. The reasoning system would be disrupted by emotion, especially for traumatic events. Time discrepancies described in the dual-systems model are also explained.